Experiences with traumatic events, consequences and care among people with visual impairment and post-traumatic stress disorder: a qualitative study from The Netherlands - Ruth M A van Nispen; Hilde P A van der Aa; Ger H M B van Rens; Alida J van der Ham; Peter Verstraten (BMJ Open)
Objective Having a visual impairment is known to be associated with an increased vulnerability to (potentially) traumatic events. Little is known about how people with visual impairment experience and process such events. This qualitative study aimed to provide more insight into experiences with traumatic events, consequences of traumatic events and post-traumatic stress disorder (PTSD)-related care among people with visual impairment and PTSD.Methods Eighteen persons with visual impairment and (a history of) PTSD were interviewed. Among them were 14 women and 4 men aged between 23 and 66 years. Recruitment of participants was done through health professionals from two low-vision service centres and a patient association for people with eye diseases and visual impairment in The Netherlands. Interviews focused on experiences with (1) traumatic events, (2) consequences of traumatic events and (3) PTSD-related care. Thematic content analysis of interview data was performed using ATLAS.ti. The COnsolidated criteria for REporting Qualitative research (COREQ) checklist was used to check for completeness and transparency of the study. Data were collected between 2018 and 2020.Results The most commonly reported traumatic events were sexual and physical abuse. Many participants experienced that their impairment had negatively affected their acceptance by others, independence and self-esteem, increasing their vulnerability for traumatic events. Additionally, having a visual impairment negatively impacted participants’ ability to respond to situations and aggravated post-traumatic stress reactions. Existing treatments seem suitable for people with visual impairment when accommodated to the impairment.Conclusions Having a visual impairment may affect traumatic events and post-traumatic stress reactions, particularly by contributing to low self-esteem, problems in social interactions and a lack of visual information. Insights from this study provide starting points for adapting pretraumatic and post-traumatic care to the needs of people with visual impairment.